Structural responses of FRP sheet piles under cantilever loading - Wilt, Joshua; Liang, Ruifeng; GangaRao, Hota; Mostoller, Jeremy (Sustainable structures, 2023)
Sheet piles are interlocked segments used for temporary or permanent soil and water retaining structures such as below-grade parking structures and sea walls. Although steel is commonly used due to its strength and ease of manufacturing, it rusts in saltwater. Fiber reinforced polymer (FRP) composite sheet piles are resistant to chlorides and have higher corrosion resistance, but their mechanical properties vary in length and width. Stress risers at corrugation corners make soil-structure interaction a challenging design issue. This research aims to develop a standardized test procedure to determine the resisting moment capacity of FRP composite sheet piles. Cantilevered FRP sheet piles fixed with a sand-concrete mixture of ~70 psi (0.48 MPa) compressive strength were tested under static loads. Strain gages and LVDTs were used to collect data on deformation response up to and beyond peak induced stress. Results suggest that the refined test procedure can assist engineers in designing efficient sheet pile structures and become a basis to develop ASTM standard.